2022
DOI: 10.3892/ijo.2022.5347
|View full text |Cite
|
Sign up to set email alerts
|

Role of macrophages in tumor progression and therapy (Review)

Abstract: The number and phenotype of macrophages are closely related to tumor growth and prognosis. Macrophages are recruited to (and polarized at) the tumor site thereby promoting tumor growth, stimulating tumor angiogenesis, facilitating tumor cell migration, and creating a favorable environment for subsequent colonization by (and survival of) tumor cells. These phenomena contribute to the formation of an immunosuppressive tumor microenvironment (TME) and therefore speed up tumor cell proliferation and metastasis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 151 publications
0
24
0
Order By: Relevance
“…M1 macrophages can switch to an M2 phenotype and vice versa based on environmental changes, such as secretion of cytokines and growth factors, as well as other conditions 17 . It is generally considered that M1 macrophages play an antitumor role in the early stage of tumour progression 22 . As the tumour progresses, influencing factors, such as abundant immune‐suppressive cytokines and low‐oxygen levels, gradually skew the polarization of TAMs into phenotypically M2 macrophages 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M1 macrophages can switch to an M2 phenotype and vice versa based on environmental changes, such as secretion of cytokines and growth factors, as well as other conditions 17 . It is generally considered that M1 macrophages play an antitumor role in the early stage of tumour progression 22 . As the tumour progresses, influencing factors, such as abundant immune‐suppressive cytokines and low‐oxygen levels, gradually skew the polarization of TAMs into phenotypically M2 macrophages 23 .…”
Section: Discussionmentioning
confidence: 99%
“…As the tumour progresses, influencing factors, such as abundant immune‐suppressive cytokines and low‐oxygen levels, gradually skew the polarization of TAMs into phenotypically M2 macrophages 23 . Many studies have shown that macrophages mainly exhibit an M2 phenotype in malignant tumours 22 . The tumour‐associated M2 macrophages then secrete immune‐suppressive cytokines and recruit immune‐suppressive cells, such as regulatory T cells (Tregs), subsequently promoting tumour growth and survival, and they also stimulate angiogenesis and metastasis 23 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, traditional Chinese medicine also exhibit a certain alleviation effect on the side effects caused by surgery, chemotherapy, and other treatments and some precancerous lesions [ 43 , 44 ]. A large number of studies have also proved that traditional Chinese medicine including Chinese herbal medicine, acupuncture, and moxibustion as well as other treatments exert their antitumor effects from multiple perspectives and multiple targets [ 44 52 ]. The antitumor mechanism of Chinese herbal medicine is shown in Figure 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Both TGF‐β1 and VEGF typically promote the polarization of macrophages to an immunosuppressive M2 phenotype. M2 macrophages themselves potentially secrete TGF‐β1 and VEGF and inhibit the recruitment and cytotoxic function of CD8 + T cells 7,8 . VEGF may be involved in hypervascularity in the tumor stroma, which could prevent CD8 + T cells from trafficking into the tumor 9 .…”
Section: Discussionmentioning
confidence: 99%
“…M2 macrophages themselves potentially secrete TGF‐β1 and VEGF and inhibit the recruitment and cytotoxic function of CD8 + T cells. 7 , 8 VEGF may be involved in hypervascularity in the tumor stroma, which could prevent CD8 + T cells from trafficking into the tumor. 9 Furthermore, HIF‐1α‐positive stromal vessels may participate partially in hypervascularity.…”
Section: Discussionmentioning
confidence: 99%